2008
DOI: 10.1292/jvms.70.193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mycotoxins on Mitogen-stimulated Proliferation of Bovine Peripheral Blood Mononuclear Cells

Abstract: ABSTRACT. The effects of mycotoxins on mitogen-stimulated proliferation of bovine peripheral blood mononuclear cells (PBMCs) were investigated. Aflatoxin B 1 (AFB 1 ), deoxynivalenol (DON) and zearalenone (ZEN) were added to cultures of PBMCs, and the proliferation responses were measured using MTT bioassays. Suppression of the proliferation of calf PBMCs by AFB 1 and DON was significantly stronger than that of cow PBMCs, whereas there were no differences in suppressive effects on PBMCs from Holstein and Japan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…For the latter substance no IC 50 could be (Charoenpornsook et al 1998), suggesting the DNA synthesis to be more vulnerable to the effects of DON than the metabolic activity (MTT assay). The age of ruminants was shown as another factor influencing the susceptibility of bovine PBMC as this cell type was more sensitive to DON when isolated from calves compared with the adult cows, while the genetic background of cows appeared to have no influence (Wada et al 2008). Using the BrdU (5-bromo-2'-deoxyuridine) assay, which is a measure for DNA synthesis, the IC 50 values for DON, 15AcDON, 3AcDON, and de-epoxy DON were 510 ng/ml (1.5 μM), 444 ng/ml (1.5 μM), 4,888 ng/ml (14.5 μM) and 23,266 ng/ml (83.1 μM) when tested on Swiss mouse fibroblasts (3T3 cells) (Eriksen et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For the latter substance no IC 50 could be (Charoenpornsook et al 1998), suggesting the DNA synthesis to be more vulnerable to the effects of DON than the metabolic activity (MTT assay). The age of ruminants was shown as another factor influencing the susceptibility of bovine PBMC as this cell type was more sensitive to DON when isolated from calves compared with the adult cows, while the genetic background of cows appeared to have no influence (Wada et al 2008). Using the BrdU (5-bromo-2'-deoxyuridine) assay, which is a measure for DNA synthesis, the IC 50 values for DON, 15AcDON, 3AcDON, and de-epoxy DON were 510 ng/ml (1.5 μM), 444 ng/ml (1.5 μM), 4,888 ng/ml (14.5 μM) and 23,266 ng/ml (83.1 μM) when tested on Swiss mouse fibroblasts (3T3 cells) (Eriksen et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Primarily being a hepatotoxin, AFB1 also exerts negative impact on immune system. It has been proved that AFB1 develops its immunotoxicity by inhibiting lymphocyte proliferation (Meissonier et al, ; Wada et al, ), reducing the number of circulating lymphocytes (Han et al, ), altering the activities of natural killer(NK) cells and disturbing the expression of cytokines (Methenitou et al, ). A recent research also showed that severe lymphocyte depletion in the thymus and bursa of Fabricius was due to apoptosis (Solcan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Each sample was cultured with 10 g/ml phytohemagglutinin (PHA; Sigma, St. Louis, MO, U.S.A.) [24] alone, PHA and DEX (Sigma; 10, 15 or 20 μg/ml) [13,20], PHA and FLU (Sigma; 10, 25 or 50 μg/ml) [2,12] or PHA and MEL (Nippon Boehringer Ingelheim Co., Ltd., Tokyo, Japan; 10, 25 or 50 μg/ml) [14]. The mitogen PHA and three AIDs were used at concentrations based on those reported for previous in vitro experiments with cattle [11,12,19] and other animal species [2,12,14].…”
mentioning
confidence: 99%
“…The concentrations of PHA and the three AIDs were as described above. PHA (10 μg/ml) [20,24] was added to each PBMC culture, which was then mixed with DEX (10 or 20 μg/ml) [13], FLU (10 or 50 μg/ml) [2] or MEL (10 or 50 μg/ml) [12] and incubated for 12 hr at 37C. PBMCs were then washed and re-suspended in TRIzol reagent (Invitrogen, Carlsbad, CA, U.S.A.) to extract RNA.…”
mentioning
confidence: 99%